2015
DOI: 10.1186/s40623-015-0307-y
|View full text |Cite
|
Sign up to set email alerts
|

Application of Kalman filtering in VLBI data analysis

Abstract: In this paper, we demonstrate the advantage of applying a Kalman filter for the parameter estimation in very-long-baseline interferometry (VLBI) data analysis. We present the implementation of a Kalman filter in the VLBI software VieVS@GFZ. The performance is then investigated by looking at the accuracy obtained for various parameters, like baseline lengths, Earth Orientation Parameters, radio source coordinates, and tropospheric delays. The results are compared to those obtained when the classical least squar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…In this research we have developed a new empirical FCN model with higher temporal resolution by fitting M a n u s c r i p t the amplitude parameters directly to the Very Long Baseline Interferometry (VLBI) solution calculated with the GeoForschungsZentrum (GFZ) version (Nilsson et al, 2015) of the Vienna VLBI Software (VieVS) (Böhm et al, 2012). A comparison with other recently determined empirical FCN models: Malkin (2013), Krásná et al (2013) and Lambert and Dehant (2007) was included by means of the weight root mean square (WRMS) of the residuals during the entire period of VLBI data.…”
Section: Introductionmentioning
confidence: 99%
“…In this research we have developed a new empirical FCN model with higher temporal resolution by fitting M a n u s c r i p t the amplitude parameters directly to the Very Long Baseline Interferometry (VLBI) solution calculated with the GeoForschungsZentrum (GFZ) version (Nilsson et al, 2015) of the Vienna VLBI Software (VieVS) (Böhm et al, 2012). A comparison with other recently determined empirical FCN models: Malkin (2013), Krásná et al (2013) and Lambert and Dehant (2007) was included by means of the weight root mean square (WRMS) of the residuals during the entire period of VLBI data.…”
Section: Introductionmentioning
confidence: 99%
“…A Kalman filter approach has been successfully used by the ITRS combination center at NASA Jet Propulsion Laboratory (JPL) for their JTRF2008 solution, providing station coordinates at weekly intervals together with secular velocities and seasonal signals . For the analysis of very long baseline interferometry (VLBI, Schuh and Behrend, 2012;Schuh and Böhm, 2013) observations, Kalman filtering was introduced by Herring et al (1990), and recently applied in studies by Nilsson et al (2015), Soja et al (2015), and Karbon et al (2015).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the datum conditions are fulfilled at the level of 0.01 mm for translations and 1 μas for rotations at every epoch. More details about the Kalman filter implementation can be found in Nilsson et al (2015).…”
Section: Methodsmentioning
confidence: 99%
“…Widely used measures to quantify the effects on station positions are station coordinate and baseline length repeatabilities (Davis et al 1985). Nilsson et al (2015) showed that by using a Kalman filter instead of least squares adjustment, an improvement in the baseline length repeatabilities of about 10 % is possible. Here, we wanted to focus on the effect of a station-specific noise model for ZWD.…”
Section: Effects On Station Coordinatesmentioning
confidence: 99%